MORFOLOGI DAN KLASIFIKASI TANAH PADA FORMASI WATURANDA DENGAN PENGGUNAAN LAHAN HUTAN DAN TEGALAN DI DESA LEBAKWANGI, BANJARNEGARA, JAWA TENGAH - Risang Sembodo Siwi; Mohammad Nurcholis; Sari Virgawati (Jurnal Tanah dan Sumberdaya Lahan, 2023)
Soil develops from the rocks of the Waturanda Formation in Lebakwangi Village is from sedimentary tertiary volcanic activity. The purpose of this study was to identify the soil morphology and soil classification in the Waturanda Formation with forest and dry land use according to the Soil Taxonomy 2014, World Reference Base 2015, and National Soil Classification 2016. The soil profile from the topsoil to subsoil under the forest land use was dominated by clay texture (49.04%-56.46%), with particle density 1.20-1.24 g cm-3, bulk density 1.64-1.82 g cm-3, pH (H2O) 4.05-4.68, pH (KCl) 3.42-3.55, organic C 1.47-2.29%, CEC 13.05-19.60 cmol(+) kg-1, and saturation base 24.35%-73.70%. Similarly, the soil profile under the dryland use was dominated by clay texture (37.06%-62.60%), with particle density 1.10-1.20 g cm-3, bulk density 1.58-1.75 g cm-3, pH (H2O) 4.32-4.54, pH (KCl) 3.49-3.65, organic C 0.96-1.66%, CEC 19.95-25.81 cmol(+) kg-1, and saturation base 58.35%-95.43%. Both soil profiles have an udic humidity regime and isohyperthermic soil temperature regime. Soil classification according to Soil Taxonomy, WRB, and NSC for forest land is Humic Eutrudepts, Clayic Haplic Luvisols, and Eutrict Cambisols, while for dryland use is Pachic Hapludolls, Clayic Haplic Luvisols, and Haplic Molisols.